Methadone Dosage and Plasma Levels, SNPs of OPRM1 Gene and Age of First Drug Use Were Associated With Outcomes of Methadone Maintenance Treatment - Peng, Sufang; Jiang, Haifeng; Du, Jiang; Lin, Shuxing; Pan, Shujun; Yu, Shunying; Zhao, Min (Frontiers in Genetics, 2018)
Object: To explore the association between methadone dosage, plasma drug concentration, SNPs of μ-opioid receptor gene (OPRM1), ATP-binding cassette sub-family B member 1 gene (ABCB1) and methadone maintenance treatment (MMT) response. Method: 240 Chinese Han participants receiving MMT were recruited in Shanghai. Nine single-nucleotide-polymorphisms (SNPs) of OPRM1 gene and three SNPs of ABCB1 gene were genotyped, plasma methadone concentration was detected and morphine urine test was taken in all subjects. Results: Methadone dosage, plasma methadone concentration, negative rate of morphine urine test of retention participants were significantly higher, although the addiction severity index (ASI) was not significantly different between the two groups. A allele and AA genotype carriers of rs562859 (OPRM1 gene) had better compliance of MMT, and AA genotype carriers had a higher negative rate of morphine urine test. However, the difference was not significant after adjusting influence factors (age, sex and methadone dosage). GG genotype carriers of rs3192723 (OPRM1 gene) had a significantly lower negative rate of morphine urine test, and the difference was still significant after adjusting influence factors. logistic regression analysis showed that methadone free trough concentration (OR=0.910, p=0.023) and AA genotype of rs526859 (OR=0.580, p=0.037) were associated with better compliance of MMT. After Bonferroni correction, only free tough concentration of methadone was negative correlated with MMT compliance. rs6912029 (OR=0.021, p=0.066) and rs6902403 (OR=0.910, p=0.007) of OPRM1 gene, age of first use (OR=1.118, p=0.005), and average methadone dosage (OR=1.033, p=0.045) were associated with MMT effect. After Bonferroni correction, average methadone dosage was no longer correlated with MMT effect. Conclusion: Dosage of methadone, plasma methadone concentration, several SNPs (rs3192723, rs6912029, rs6902403) of OPRM1 gene, and age of first drug use were associated with better MMT outcomes.